IMPERATIVE VERBS IN PREDICATIVE FORMS - Mashosh, Ali Adnan; Owaid Mohammed, Iman (Al-Adab Journal, 2022)
The article has an attempt to consider the verb in Imperative Mood as the predicative center of the sentence. The attention is focused on the way as a morphological category, which, in contrasting the forms of real, imperative and conditional ways, relates action to reality. In Russian it can be represented as Real, Conditional and Imperative Mood, which are contrasted with each other by the notation of reality (real way) – unreality (conditional and imperative ways) of action. It is explained that the predicative core of a sentence is subject and predicate. This thesis allowed us to outline two views on the problem of the verb in the imperative: the first is the verbocentricism, when the verbal predicate is the starting point for the deployment of the constructive composition of the sentence, i. e. the predicates are the core of abstract semantic syntagmas, and the actants are concretisations of the semantic predicates of valences; the second is an anti verbocentric, or systemic, when the third place in the scheme is determined not by a verb, but by an attitude.